development of practical guidelines for acid base titration based on local wisdom in chemistry education study programs - Pratiwi, Bella; Masriani, Masriani; Hadi, Lukman (Universitas Tanjungpura, Prodi Pendidikan Kimia, 2023)
This research aimed to determine feasibility and student response to worksheet of instrumentation chemical practicum based on local wisdom. It is developed based on test results the expert (expert judgment) and field trials. This research method was the research and development (RD) which adopt a development model Borg Gall. Subject of this research is a chemistry student practicum instraction based on local wisdom that tested the students of Chemistry Education FKIP Tanjungpura University in early trials and major field trials. The results of data analisis showed that chemistry student worksheet based on local wisdom is very proper to use in learning of the content feasibility of 93,33%, presentation feasibility of 91,67%, linguistic feasibility of 93,33%, chart feasibility of 91,67%. The student response initial field trials of 86,16%, and the main field trials of 81,04%. It showed that the level of chemistry student worksheet based on local wisdom belongs to very high criteria.